Implementasi Penilaian Autentik Kurikulum 2013 Pada Mata Pelajaran PAI dan Budi Pekerti di SDN 1 Bangunrejo Ponorogo - Habibi, Mukhlas; Lestari, Fina Aulika; Afif, Yusmicha Ulya (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
Assessment is an important part of education, because with the assessment educators can see the extent to which the success of the learning process and the abilities of students. There are various types of assessments to measure students' abilities, in the 2013 curriculum there is an assessment model called authentic assessment. Authentic assessment is a comprehensive assessment that not only assesses students' cognitive mastery, but also assesses affective and psychomotor mastery. Educators who conduct authentic assessments of students will get the right assessment results, but sometimes there are still educators who use authentic assessments but are not in accordance with the competence of students. This study aims to reveal the problems that often occur, namely the discrepancy between the value and ability of students in mastering the subject matter. This research is a qualitative research. In the collection using observation techniques, interviews, and documentation.